PENGARUH HEDONIC MOTIVES TERHADAP IMPULSE BUYING MELALUI BROWSING DAN SHOPPING LIFESTYLE PADA ONLINE SHOP - LUMINTANG, FENNY FELICIA (Universitas Katolik Widya Mandala Surabaya, 2012)
Developments in information technology are increasing rapidly in recent years have also brought spending in modern retail stores experience any impulse buying when shopping. Impulsive buying occurs when a consumer sees a particular product or brand, then consumers become interested to get it, usually due to a stimulation of the highlights of the store. Additionally hedonic motivation is the motivation of consumers to shop because shopping is a pleasure to notice the benefits of the product purchased. This study aimed to determine the relationship between Hedonic Motives relation to Impulse Buying through Browsing and Shopping Lifestyle on online shop. The object of research is the student in Surabaya who've been made a purchase on websites that exist online. The samples were used as much as 126 respondents and using analytical SEM (Structural Equation Modeling) with LISREL 8.70 program. The findings obtained from the research are H1, H2, H3, and H5 has significant influence, whereas H4 and H6 had no significant effect. Limitations of this research study are the number of respondents is small enough that it can not represent the total number of students in Surabaya.